Prevalence and Differences of Depression, Anxiety, and Substance Use Between Chinese College-Age Students Studying in China and America During the Coronavirus Disease 2019 Pandemic - Li, Mingsheng; Sun, Wangdi; Wang, Ye; Qi, Chang (Frontiers in Psychiatry, 2022)
Introduction: The Coronavirus disease swept the globe and harmfully influenced the mental health and behaviors of the college student population. This study aims to examine the prevalence and difference of mental health and the substance use problems of the Chinese college-age students who are studying in China (CSC) and America (CSA) during the COVID-19 pandemic. Methods: 1504 students participated in this study. 42.12% of students are enrolled in Chinese colleges and 57.78 % of students are enrolled in American colleges, aged from 17 to 23 years old (x ̅±s = 19.90 ± 1.50). Binary logistic regression and independent t-test were used in this study to find the predict variables and association among mental health, substance use problems, and student population. Results: The two student groups had a statistical difference in GAD-7, alcohol, medicines, drinks, drugs and cigarettes (p < .01). The students suffering depression problems from two groups have statistical significance with drinks [OR = 0.89, 95% CI = 0.81 - 0.97, p < 0.05; OR = 1.11 95% CI = 1.04 - 1.19, p < .01]. CSA experiencing anxiety problem had a significant association with alcohol, drinks, cigarette and desserts (p < .05). Conclusion: This is the first cross-sectional study focusing on the comparison of the Chinese college-age students' mental health and substance use problems who are studying in China and America during the pandemic. Our study revealed severe mental health and substance use problems in both student groups, particularly in the CSA during the COVID-19. The findings of our study also highlight the evidence to find more interventions and preventions to solve the different mental health and substance use problems for college students.